Coresidency, Ethnicity, and Happiness of China's Rural Elders - Rachel Connelly; Michael Iannotti; Margaret Maurer-Fazio; Dandan Zhang (Institute for the Study of Labor (IZA), 2014)
As China moves into the ranks of aged societies, coresidency of elders with their adult children has become an increasingly important policy concern. This article utilizes data from the 2000 Population Census of China and the 2011 Chinese Household Ethnicity Survey (CHES) to analyze coresidency patterns of rural elders in seven Chinese provinces with high concentrations of ethnic minority populations. We also explore one consequence of coresidency, reported happiness. We find that socioeconomic variables matter in the determination of coresidency in China in ways that are very similar to their roles in other countries. However, changes between 2000 and 2011 in the effects of age and widowhood show that coresidency decisions among rural elders provinces are transitioning from child-centric to parent-centric. Our analysis also reveals the large role cultural norms play in determining coresidency, as evidenced by differences across ethnic groups. The CHES data allow us to compare coresidency across ethnicity with respect to both individual and regional degrees of assimilation versus isolation. Elders who do not speak Mandarin have higher rates of coresidency than those who do. Additionally, those who live in counties with low rates of intermarriage and intergroup friendships are also more likely to coreside. In exploring the determinants of happiness, we find again that socioeconomic and demographic conditions matter, as does ethnicity. Controlling all else, coresidency increases the happiness of the elderly by about 28 percent. Moreover, the unobserved characteristics that drive coresidency are highly detrimental to the happiness of the elderly.
Keywords: D13; J12; J14; J15; 330; coresidency; happiness; ethnicity; Minzu; global life satisfaction; elders; living arrangements; China Household Ethnicity Survey; China